2021
DOI: 10.5530/pj.2021.13.204
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Activity of Extract and Fractions of Castanopsis costata Leaves on Alloxan-induced Diabetic Mice

Abstract: Indonesia has the world's country second largest forest biodiversity, with 28,000 plant species, of which 2,500 species, including Castanopsis costata, commonly known as "Cep-cepan", are used as medicine. 9-10 C. costata belongs to the Fagaceae family and has been known to exhibit therapeutic activities, for instance, anti-fever, digestive issue alleviation, and analgesic properties. 11 According to previous studies, C. costata exhibits numerous biological properties, including antioxidant activity, 12 antiinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 12 publications
0
12
0
3
Order By: Relevance
“…This might be due to the active compounds contained in the extract. A previous study showed that EECC contains several secondary metabolites, including polyphenols, flavonoids, alkaloids, tannins, saponins, and triterpenes [23,24]. Furthermore, several studies have reported flavonoid compounds' antipyretic and antioxidant activities [25][26][27].…”
Section: Antipyretic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…This might be due to the active compounds contained in the extract. A previous study showed that EECC contains several secondary metabolites, including polyphenols, flavonoids, alkaloids, tannins, saponins, and triterpenes [23,24]. Furthermore, several studies have reported flavonoid compounds' antipyretic and antioxidant activities [25][26][27].…”
Section: Antipyretic Activitymentioning
confidence: 99%
“…Indonesia has the second-largest forest biodiversity in the world, with 28,000 plant species, of which 2,500 species, including Castanopsis costata, commonly known as "Cep-cepan," are used medicinally [8]. C. costata is known to have therapeutic activity as an antipyretic, relieve digestive problems, analgesic, and antidiabetic [9,10]. Traditionally, this plant is often used to treat fever, but no studies have confirmed this effect.…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia merupakan negara kedua dengan keanekaragaman hayati terbesar di dunia dengan hutan tempat ditemukannya 28.000 spesies tumbuhan. Diperkirakan sekitar 2.500 jenis tumbuhan berpotensi berkhasiat obat (Elfahmi et al, 2014;Alkandahri et al, 2019). Castanopsis costata, atau yang biasa disebut dengan "Cep-cepan", merupakan salah satu tanaman yang digunakan secara empiris sebagai obat antidiabetes oleh masyarakat Sumatera Utara, Indonesia.…”
Section: Pendahuluanunclassified
“…Castanopsis costata, atau yang biasa disebut dengan "Cep-cepan", merupakan salah satu tanaman yang digunakan secara empiris sebagai obat antidiabetes oleh masyarakat Sumatera Utara, Indonesia. Hasil penelitian terbaru saat ini telah melaporkan bahwa ekstrak dan fraksi daun Cep-cepan mempunyai efek antidibetes yang di uji secara in vivo (Alkandahri et al, 2021). Aktivitas antidibetes dari tumbuhan Cep-cepan diduga karena senyawa flavonoid yang terkandung didalamnya (Alkandahri et al, 2016).…”
Section: Pendahuluanunclassified
“…In Indonesia, several ethnic groups have started using allopathic medicines together with ethnomedicine [5]. There is still a lack of documentation on herbal medicinal plants, making it necessary Since 2002 to search for information on their ethnomedicine knowledge for the treatment of diseases.…”
Section: Introductionmentioning
confidence: 99%